Common and Country-specific Fluctuations in Productivity, Investment, and the Current Account - Allan W. Gregory; Allen C. Head (Queen's University, Department of Economics, 1996)
Dynamic factor analysis and Kalman filtering are used to construct a measure of common economic activity for the G7 countries. Common movements are important in productivity, but account for a substantially smaller share of movements in investment, and virtually none of the variation in the current accounts. For all seven countries, country-specific investment fluctuations have a significant negative impact on the current account, while country-specific productivity movements have little effect. A multi-country dynamic general equilibrium model is analyzed which is consistent with our qualitative findings. The model overstates, however, the quantitative importance of investment fluctuations for movements in the current account.
Keywords: F41; C32; 330; kalman filter; current account; Solow residual; investment; G7